Human papillomavirus infection – new perspectives on diagnosis and treatment (review) - N V Bestaeva; N M Nazarova; V N Prilepskaya; D Yu Trofimov; O V Burmenskaya; L A Sulamanidze (Гинекология, 2013)
In the present review analyzed data from epidemiological studies of the prevalence of different types of human papillomavirus (HPV) on the Asian and European regions and their relationship with the development of cervical intraepithelial neoplasia and cervical cancer. The data of the literature on the little-known high-risk HPV types of HPV 52 and 58. Questions of risk of a persistention HPV, depending on the type of HPV, duration of a persistention, age of the woman, as the most important factor in the progression of pre-cancer and cervical cancer are considered.